A Normative Modeling Method for Complex Gear Coupled Rotor-bearing System Dynamics - Xia Boqian; Jiang Xi; Zhang Zebin (Jixie chuandong)
Due to the coupling effect of gears, the vibration of each rotor in the gear rotor bearing system is coupled and affected by each other. The study of the dynamics of the gear rotor bearing system must be analyzed based on a systematic and holistic concept. Therefore, the dynamic modeling and model reduction of the gear rotor bearing coupling system have always been a common concern. Based on the basic principle of gear meshing, this study establishes the geometric coupling model (or called kinematic coupling model) of the spur gear pair, helical gear pair, spur bevel gear pair and spiral bevel gear pair; and by using the transformation matrix of the coupling model, a unified, convenient and normative modeling method for the dynamic study of arbitrary complex gear-rotor-bearing coupled system including the above four kinds of gear pairs is given, which provides convenience for the dynamic study of complex gear shafting.